The tyrant's tomb - Riordan, Rick (Riordan, Rick. Trials of Apollo, 2019)
Apollo has been cast out of Olympus by his father, Zeus, and given a human name and identity--he is now Lester, a pathetic mortal, whose birthday is April eighth. So says his horrendous driver's license. On Earth, Apollo-Lester must face the imminent attack on Camp Jupiter by the emperors Caligula and Commodus, face down the evil Blood Moon king and his armies of the undead, and suffer the wrath of the Cumaean Sibyl, who still hasn't forgiven him.